ChemInform Abstract: Methods for Identifying and Characterizing Interactions Involving RNA. Issue 10 (7th March 2013) - Blakeley, Brett D.; DePorter, Sandra M.; Mohan, Utpal; Burai, Ritwik; Tolbert, Blanton S.; McNaughton, Brian R.
Abstract Review: 155 refs.